Growth and survival of giant gourami juvenile immersed in freshwater containing growth hormone - Ratnawati, Pustika; Alimuddin, .; Arfah, Harton; Sudrajat, Agus Oman (Indonesian Society of Scientific Aquaculture (ISSA), 2012)
Growth of giant gourami is relatively slow. Administration of recombinant growth hormone (rGH) by severaltimes immersion in water containing 0.9% NaCl for one hour can significantly increase the growth. In thisstudy, giant gourami juvenile were immersed in freshwater containing 120 mg/L rGH to determine the longimmersion time that provides higher growth and survival. Juvenile at seventh-day-old after egg yolk absorbedwas immersed for 0.5, 1.0, 2.0, and 3.0 hours in rGH solution. As controls, fish was immersed in freshwaterwithout rGH (control 1: C1), and water containing 0.9% NaCl, and 120 mg/L rGH (control 2: C2). Fish waskept under controlled conditions in 20 L aquarium for three weeks, then in 50 L aquarium until at end ofexperiment, and fed at satiation. The results showed that highest growth in body weight, survival, and biomass(p<0.05) were obtained in rGH immersion treatment for 0.5 hour. Biomass of fish immersed by rGH for 0.5hour was about 32% higher compared to control C1, and 13% compared to C2. Survival of the 0.5 hour rGHimmersedfish (100%) was similar to control C1 and C2. Thus, immersion of giant gourami juvenile infreshwater containing rGH for 0.5 hour allowed highest growth rate, and this method is relatively easy to beadopted by fish hatchery.Keywords: immersion, hormone, growth, freshwater, giant gourami